Angiojet System Used in the Treatment of Submassive Pulmonary Embolism: A Case Report of Two Patients - Jinbo Liu; Tianrun Li; Wei Huang; Na Zhao; Hongwei Zhao; Hongyu Wang (Case Reports in Vascular Medicine)
Background. Massive or submassive pulmonary embolism (PE) carries a high mortality. Percutaneous mechanical thrombectomy using the Angiojet system is accepted for the treatment of PE. Here, we reported two submassive PE cases who were treated with the Angiojet system successfully, to provide some advice for the therapy of submassive PE. Method. Two patients with suffocation were admitted to our hospital. One patient was accompanied by lower blood pressure (20% lower than basal blood pressure) and higher pulmonary artery pressure (89 mmHg); the other patient had larger right ventricular transverse diameter (46 mm), decreased left ventricular end diastolic anteroposterior diameter (34 mm), and higher heartbeats (107 heartbeats per minute). Pulmonary artery computed tomography angiography showed bilateral pulmonary embolism. Result. The Angiojet system with a high-pressure jet spray pattern (urokinase 25 wiu+sodium chloride injection 50 ml) was used. Intravascular thrombolysis by urokinase (100 wiu/day for 1 day) was done after being back in the ward. And low molecular weight heparin was used in hospitalization, and rivaroxaban was used after discharge. Both patients were treated successfully. However, the level of platelet was significantly lower in one patient after Angiojet system usage and recovered to the preoperative level the next day. Another patient suffered from bradyarrhythmias during the usage of Angiojet, and bradyarrhythmias disappeared when the Angiojet system stopped. Pulmonary embolism was cured after 3 months in both patients. Conclusion. Angiojet could be a simple, safe, and well-tolerated treatment for massive or submassive PE. And hematocrit, platelet, kidney function, and heart rhythm should be monitored during perioperation.